Women farmers held back by traditions - Njuki, Jemimah (International Livestock Research Institute, 2011)
Jemimah Njuki explained that two facts have hindered women’s development in agriculture: lack of ability to inherit land and other rules stemming from traditional cultures and the fact that most policymakers are men; changes are now occurring in both areas.